2018
DOI: 10.3791/58598
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Multiple Myeloma Cell Growth In Vivo by Single-wall Carbon Nanotube (SWCNT)-delivered MALAT1 Antisense Oligos

Abstract: The single-wall carbon nanotube (SWCNT) is a new type of nanoparticle, which has been used to deliver multiple kinds of drugs into cells, such as proteins, oligonucleotides, and synthetic small-molecule drugs. The SWCNT has customizable dimensions, a large superficial area, and can flexibly bind with drugs through different modifications on its surface; therefore, it is an ideal system to transport drugs into cells. Long noncoding RNAs (lncRNAs) are a cluster of noncoding RNA longer than 200 nt, which cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These include pharmacologic inhibitors of STAT activation (e.g., ruxolitinib) as well as exogenous expression of SOCS3 via viral vectors (7,24,25) and administration of SOCS peptides (8,26). STAT inhibitors, while promising in hematological cancers such as multiple myeloma (27), failed in clinical drug trials of solid tumors owing to toxicity and tumor resistance due to pathway compensation (28). Viral transduction of SOCS3 expression has not yet been tested in humans in vivo; therefore, its effectiveness and safety at this point are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These include pharmacologic inhibitors of STAT activation (e.g., ruxolitinib) as well as exogenous expression of SOCS3 via viral vectors (7,24,25) and administration of SOCS peptides (8,26). STAT inhibitors, while promising in hematological cancers such as multiple myeloma (27), failed in clinical drug trials of solid tumors owing to toxicity and tumor resistance due to pathway compensation (28). Viral transduction of SOCS3 expression has not yet been tested in humans in vivo; therefore, its effectiveness and safety at this point are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[88,106,107,140,142,[150][151][152]. MALAT1 gapmer oligonucleotides conjugated to single-walled carbon nanotubes delivered systemically into mice resulted in significant inhibition of multiple myeloma growth [153]. Further, small molecules specifically targeting the MALAT1 triple helix structure have been identified and they lay the foundation for new classes of anticancer therapeutics for the treatment and investigation of MALAT1-driven cancers [154].…”
Section: Therapeutic Targeting Of Malat1mentioning
confidence: 99%
“…SWCNT and SWCNT-COOH carbon nanoparticles are well-investigated and show good potential as nucleic acids delivery agents [ 27 ]. They have been employed for delivery of siRNA [ 35 , 36 , 37 , 38 ], antisense oligonucleotides [ 39 ], and DNA [ 40 , 41 ]. Earlier we showed that the IC 50 values for the SWCNT-oligonucleotide hybrids are not achieved even at hybrid concentrations of 100 mg/L [ 28 ].…”
Section: Resultsmentioning
confidence: 99%